How Does Brand Storytelling Build Brand Loyalty? The Case of Gojek Advertising Campaign - Salim, Laras Luthfiyah; Hudrasyah, Herry (Journal of Business and Management, 2019)
The purpose of this study was to determine the relationship of Brand Storytelling to Perceived Brand Image and its impact on Emotional Brand Attachments and Brand Loyalty. The survey was conducted on 175 Gojek users aged 19-24 who had watched one of the four Gojek campaign advertisements on Youtube that were used as the object of research. The campaign ad in question is a video with the tagline #HidupTanpaBatas, #GojekVersiKamu, #CariPahala, and #AnakBangsaBisa. The results of the study show 1) Brand storytelling has a significant effect on the perceived brand image with C.R. 4.370 and estimate 0.847; 2) Perceived Brand Image has a significant effect on Emotional Brand Attachments with C.R. 3.395 and estimate 0.571; 3) Perceived Brand Image does not significantly influence brand loyalty with C.R. 0.051 and estimate 0.009; 4) Emotional Brand Attachments have a significant effect on Brand Loyalty with C.R. 3.021 and estimate 0.636. The findings in this study indicate that Brand Storytelling is one of the marketing strategies that are effective in forming Perceived Brand Image so that it can influence Brand Loyalty with the Emotional Brand Attachment. Data testing and processing using AMOS SEM version 22.Â Keywords: Brand Storytelling, Perceived Brand Image, Emotional Brand Attachment, Brand Loyalty, Quantitative Research, SEM AMOSThe purpose of this study was to determine the relationship of Brand Storytelling to Perceived Brand Image and its impact on Emotional Brand Attachments and Brand Loyalty. The survey was conducted on 175 Gojek users aged 19-24 who had watched one of the four Gojek campaign advertisements on Youtube that were used as the object of research. The campaign ad in question is a video with the tagline #HidupTanpaBatas, #GojekVersiKamu, #CariPahala, and #AnakBangsaBisa. The results of the study show 1) Brand storytelling has a significant effect on the perceived brand image with C.R. 4.370 and estimate 0.847; 2) Perceived Brand Image has a significant effect on Emotional Brand Attachments with C.R. 3.395 and estimate 0.571; 3) Perceived Brand Image does not significantly influence brand loyalty with C.R. 0.051 and estimate 0.009; 4) Emotional Brand Attachments have a significant effect on Brand Loyalty with C.R. 3.021 and estimate 0.636. The findings in this study indicate that Brand Storytelling is one of the marketing strategies that are effective in forming Perceived Brand Image so that it can influence Brand Loyalty with the Emotional Brand Attachment. Data testing and processing using AMOS SEM version 22. Keywords: Brand Storytelling, Perceived Brand Image, Emotional Brand Attachment, Brand Loyalty, Quantitative Research, SEM AMOS